The Acting Chair's Summing Up Independent Evaluation Office-IMF Engagement with Small Developing States : Executive Board Meeting May 6, 2022. (Policy Papers; Policy Paper ;, 2022)
Executive Directors welcomed the report of the Independent Evaluation Office (IEO) on IMF Engagement with Small Developing States (SDS) and appreciated its insights and recommendations. They welcomed the report's finding that the Fund has substantially stepped up its engagement with its SDS members over the past decade, and that SDS country officials generally considered Fund surveillance and capacity development (CD) activities of high quality and well-tailored to their needs.